2004
DOI: 10.1080/16501970410027494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four outpatient educational programmes for patients with longstanding fibromyalgia

Abstract: More comprehensive programmes did not produce better results at group level. Also short and less costly interventions based on educational and cognitive principles were valuable for persons with longstanding fibromyalgia. More attention must be given to evaluating the clinical effect of programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
8
0
4
Order By: Relevance
“…Symptoms related to fibromyalgia are commonly amplified by high levels of stress over a long period of time (Wyalonis & Heck, 1992). Henriksson, Carlsberg, Kjällman, Lundberg and Henriksson (2004) reported that pain gradually had spread from being “localized” to being “wide-spread” in 80% of a group of patients with fibromyalgia. Presumably, the fibromyalgia syndrome cannot be explained and understood by a single biomedical predictor only.…”
mentioning
confidence: 99%
“…Symptoms related to fibromyalgia are commonly amplified by high levels of stress over a long period of time (Wyalonis & Heck, 1992). Henriksson, Carlsberg, Kjällman, Lundberg and Henriksson (2004) reported that pain gradually had spread from being “localized” to being “wide-spread” in 80% of a group of patients with fibromyalgia. Presumably, the fibromyalgia syndrome cannot be explained and understood by a single biomedical predictor only.…”
mentioning
confidence: 99%
“…However, our results diVer from those obtained by Solomon and collaborators [17] who found no diVerences in a 4-month analysis of a controlled and randomized program for patients diagnosed with osteoarthritis, rheumatoid arthritis or FM receiving a 6-week course and in whom the levels of disability, pain, mental health, selfeYciency and satisfaction did not change during the analysis in any of the groups, with respect to the control group. However, this lack of eYcacy was conWrmed by Henriksson and collaborators [20], who designed four prospective, non-randomized, long-term programs for 191 patients with FM, collecting data before the program, immediately following the program, at 1 year from program completion, using the participants as their own controls.…”
Section: Discussionmentioning
confidence: 97%
“…EVects of exercise on fatigue, sleep quality, anxiety and depression in patients with FM have been studied less frequently than the eVects on pain or other symptoms [20,21]. Fontaine and collaborators [22] evaluated the eVects of exercise on 73 sedentary adults with FM, randomized, in a 12-week program to moderately increase the intensity of physical activity, consisting of 30-min sessions of self-selected lifestyle physical activity, 5-7 days a week.…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary approach combining each of these modalities may be the most beneficial. Other 105 1 1 Educational programs 106 1 1 CBT 107 1 1 Hair analysis 108 1 1 Surface EMG 109 1 1 Thyroid hormone 110 1 1 Water therapy 111 1 1 Chiropractic manipulation and cranial electrical stimulation 112 1 1 Acupuncture and diet 113 1 1 Survey of CAM therapies used by FMS patients referred to Mayo clinic 116 1 1 Psychologic profile of FMS attending private chiropractic clinics 117 1 1…”
Section: Published Guidelines Found On the Ngcmentioning
confidence: 99%